„Twórczość obca nam klasowo” – analiza komunikacyjno-językowa doniesień agenturalnych, informacji, notatek i uwag osobowych źródeł informacji (OZI) o środowisku literackim w latach 1956–1990 - Pajewska, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The purpose of the article is to present a communication and language analysis of agent texts on the Polish literary environment prepared by personal sources of information in the years 1956–1990. Their selection was made by employees of the Institute of National Remembrance from the Warsaw branch of the Commission for the Prosecution of Crimes against the Polish Nation in a monograph entitled „Twórczość obca nam klasowo”. Aparat represji wobec środowiska literackiego 1956–1990 [“Creativity foreign to our class.” Apparatus of repression against the literary environment from 1956 to 1990]. The analysis applies only to materials that are a direct record or development of a specific denunciation filed by a person registered as a source of information, but does not apply to reports, analysis of situations, statements and other texts authored by the officers of the Security Service. These are sixty-three formally diverse texts consisting of reports, information, notes and remarks from secret collaborators (TW – Tajny Współpracownik), operational contacts (KO – Kontakt Operacyjny), confidential contacts (KP – Kontakt Poufny) and consultants (K – Konsultant). Primarily, the analysis takes into account all description elements of the act of communication and makes an introduction into discourse analysis of secret agent materials originating from the three stages of the Polish People’s Republic. Denunciation resulting in those texts fulfils a social function as a tool for political fight against the opposition and a political function as well, allowing for spreading the belief in the omnipotence of the state and destroying the existing systems of values. The texts are mainly informative, although they are not devoid of emotion expressed linguistically in a variety of ways. The authors are aware of the value of the knowledge conveyed in the texts and of the consequences of denunciation for the people they concerned.